Socio demographic, clinical and side effect profile of electroconvulsive therapy use among psychiatric inpatients: a cross sectional study from South East Asia - Kashmir - Dar, Mohammad Maqbool; Shoib, Sheikh; Mushtaq, Raheel; Manhas, Rameshwar Singh (International Journal of Research in Medical Sciences, 2017)
Background:Electroconvulsive Therapy (ECT) is a neuromodulative technique, which is effective but underutilized for treatment of psychiatric disorders. The aim of the study was to investigate socio demographic, clinical and side effect profile of electroconvulsive therapy use among psychiatric inpatients. Methods:A cross sectional study was performed for a period of 1 year in postgraduate department of psychiatry (Institute of mental health and neurosciences Kashmir - center of excellence). Patients of pharmacotherapy resistant psychiatric disorders attending the hospital during this period were taken in study. The data was recorded in a specially designed proforma which documented the socio-demographic variables including age, sex, residence, occupation, socioeconomic status was recorded. Chi-square, Fisher exact, and t tests were used to note the statistically significant association. Results:The mean age of the study sample was 39.6 (±11.76) years. Maximum number of patients were in the age group 41-50 years i.e. 16 (28.6%), followed by 31-40 years i.e. 15 (26.8%). The mean number of ECT’s received was 8.22 (±2.073). About 29 (51.8%) patients reported body aches, 24 (42.9%) patients reported forgetfulness, 9 (16%) patients reported headache and only 1 (2%) patient reported agitation. Conclusion:The results indicate that electroconvulsive therapy is used in all psychiatric disorder with fewer side effects in pharmacotherapy resistant psychiatric disorders.